Prognostic significance of mucinous histology in metastatic colorectal cancer patients treated with regorafenib - ARIKAN, RUKİYE; DEMİRCAN, NAZIM CAN; YAŞAR, ALPER; SEVER, NADİYE; ÇELİKEL, ÇİĞDEM; SARI, MURAT; KÖSTEK, OSMAN; BAYOĞLU, İBRAHİM VEDAT (My University, 2023)
Objective: Prognostic factors for regorafenib therapy have not been fully defined. Mucinous adenocarcinoma (MAC) is a dis-tinct subtype of colorectal cancer (CRC). We investigated the significance of mucinous histology in patients treated with regorafenib for metastatic CRC (mCRC). Material and Methods: In this retrospective study, patients were stratified according to the presence of mucinous histology; >1% extracellular mucin was defined as mucinous component adenocarcinoma (MCAC), and containing no mucin was defined as non-MAC. The prognostic significance of mucinous histology for progression-free survival (PFS) and overall survival (OS) was evaluated by univariate and multivariate analyses. Results: A total of 103 patients were included, including 20 (19.4%) patients with MCAC and 83 (80.6%) patients with non-MAC. The median follow-up time was 8.6 months (range 1.8-31.6 months). The median PFS was lower in cases with MCAC than those with non-MAC (3.2 months vs. 3.6 months, respectively, p=0.01). Median OS was lower in MCAC patients than in non-MAC patients (4.3 months vs. 9.6 months, respectively, p=0.008). In multivariate analyses, mucinous histology was an independent risk factor [haz-ard ratio (HR): 2.2, p=0.003] for PFS and Eastern Cooperative Oncology Group-Performance Status (HR: 2.2, p=0.01), cancer antigen 19-9 (HR: 1.7, p=0.03), and mucinous histology (HR: 1.9, p=0.02) were independent risk factors for OS. Conclusion: This study revealed the prognostic value of mucinous histology in mCRC patients treated with regorafenib. Consideration of histologic features may be helpful in se-lecting patients for regorafenib therapy.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ONKOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ONCOLOGY; colorectal neoplasms; Mucinous adenocarcinoma; prognosis; regorafenib; Mucinous adenocarcinoma; colorectal neoplasms; regorafenib; prognosis